2003
DOI: 10.1002/macp.200390057
|View full text |Cite
|
Sign up to set email alerts
|

Homo‐ and Copolymerization of Norbornene and Styrene with Pd‐ and Ni‐Based Novel Bridged Dinuclear Diimine Complexes and MAO

Abstract: Novel bridged dinuclear diimine nickel and palladium complexes catalyzed the vinyl addition polymerization of norbornene at a single active site with high activity. The latter exhibited higher activity than the former. Smaller substituents around the imido group in the ligand were more favorable for increasing the activity than bulkier ones. The polynorbornenes were all noncrystalline but had short‐range order and their glass transition temperature, Tg, ranged from 270 to 400 °C. Furthermore, the random copoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 24 publications
10
37
0
2
Order By: Relevance
“…The system Pd-16/MAO was used to study the influence of the polymerization conditions on the catalytic activity. When the molar Al/Pd ratio was decreased from 525 to 35, the activity also decreased, but still remained in the area of 10 5 g PNB /mol Pd h. Furthermore, the activity decreased with a decrease of the monomer concentration [147].…”
Section: Nn-chelate Ligandsmentioning
confidence: 93%
See 1 more Smart Citation
“…The system Pd-16/MAO was used to study the influence of the polymerization conditions on the catalytic activity. When the molar Al/Pd ratio was decreased from 525 to 35, the activity also decreased, but still remained in the area of 10 5 g PNB /mol Pd h. Furthermore, the activity decreased with a decrease of the monomer concentration [147].…”
Section: Nn-chelate Ligandsmentioning
confidence: 93%
“…The dinuclear diimine complex Ni-39, activated with MAO, generated polynorbornene with moderate activity in the range of 10 5 g polymer /mol Ni h and was also applied for the copolymerization of norbornene with styrene [147].…”
Section: Nn-chelate and Bis(n) Ligandsmentioning
confidence: 99%
“…The vinylic polymerization of norbornene, yielding a 2,3-connected, rotationally strongly constrained vinyl-type polynorbornene, has been considerably attracted because of the polymer having unique physical properties, such as high glass transition temperature, optical transparency, and low birefringence [5,6]. The vinyl-type polybnorbornene can be prepared using metal complexes based on nickel [7][8][9][10][11][12][13][14][15][16], chromium [17], titanium [18][19][20][21][22][23][24], zirconium [25][26][27][28], iron [29], cobalt [30][31][32], and palladium [16,[33][34][35][36][37][38][39][40][41][42] as catalyst. Zirconocenes and cationic palladium complexes are two types of important catalysts for the vinylic polymerization of norbornene.…”
Section: Introductionmentioning
confidence: 99%
“…Sun and coworkers have reported the MMA polymerizations by neutral Pd and Ni analogs in which the Pd system showed activity almost double of its Ni analog [28]. Similar observation was also reported for the homoand copolymerization of norbornene and styrene with a binuclear Ni and Pd based diimine complexes [29]. It has also been reported that too high and low steric bulk leads to decrease the catalytic activity in MMA polymerization [30].…”
Section: Mma and Pmma Characterizationsmentioning
confidence: 62%